2015
DOI: 10.1039/c5mb00555h
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equilibrium of endogenous selenium nanoparticles in selenite-exposed cancer cells: a deep insight into the interaction between endogenous SeNPs and proteins

Abstract: Elemental selenium (Se) was recently found to exist as endogenous nanoparticles (i.e., SeNPs) in selenite-exposed cancer cells. By sequestrating critical intracellular proteins, SeNPs appear capable of giving rise to multiple cytotoxicity mechanisms including inhibition of glycolysis, glycolysis-dependent mitochondrial dysfunction, microtubule depolymerization and inhibition of autophagy. In this work, we reveal a dynamic equilibrium of endogenous SeNP assembly and disassembly in selenite-exposed H157 cells. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…49 It has been reported that elemental selenium exists as endogenous SeNPs in H157 cell line and induces cytotoxicity by many mechanisms such as inhibition of glycolysis, glycolysis-dependent mitochondrial dysfunction, and so on. 50 Microscopic observation of 4T1 cells treated with SeNPs showed a dose-dependent reduction in cell number, loss of cell-to-cell contact and cell shrinkage ( Figure 10A-D). The same cellular morphologic changes were observed when MCF-7 cells were treated with selenium nanorods synthesized by S. bikiniensis strain Ess_amA-1.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…49 It has been reported that elemental selenium exists as endogenous SeNPs in H157 cell line and induces cytotoxicity by many mechanisms such as inhibition of glycolysis, glycolysis-dependent mitochondrial dysfunction, and so on. 50 Microscopic observation of 4T1 cells treated with SeNPs showed a dose-dependent reduction in cell number, loss of cell-to-cell contact and cell shrinkage ( Figure 10A-D). The same cellular morphologic changes were observed when MCF-7 cells were treated with selenium nanorods synthesized by S. bikiniensis strain Ess_amA-1.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…38 BSeNPs are also reported to exhibit significant anticancer activity against H157 lung cancer cell line, fibrosarcoma cell line and A375 human melanoma. 5,48,50,51 Oral administration of SeNPs can enhance immune response in mice bearing 4T1 breast cancer tumor. 52 …”
Section: Cell Viability Assaymentioning
confidence: 99%
“…There are very attractive suggestions that gut microbiota can oxidize nano-Se into selenite/selenate or reduce it into H 2 Se with the following synthesis of selenoproteins [ 6 , 7 ]. Recently, some experimental evidence have been provided to prove that nano-Se particles can be dissolved and oxidized to inorganic oxoanions of Se in the gut in the presence of microbiota before their absorption [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some experimental evidence have been provided to prove that nano-Se particles can be dissolved and oxidized to inorganic oxoanions of Se in the gut in the presence of microbiota before their absorption [ 6 ]. Furthermore, a hypothetical schematic diagram showing an intracellular dynamic cycle of endogenous selenium nanoparticles (SeNPs) was proposed [ 7 ]. In fact, it was suggested that elemental selenium could be re-oxidized by superoxide radicals into selenite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation